Ethnographic Approaches to Remote Digital Culture - Ibrahim, shakeela; Dr. Muhammad Manshoor Hussain Abbasi (Journal of Peace, Development and Communication, 2024)
The purpose of this study is to analyze the relationship between culture and community, which are becoming more obscure in the quickly changing world of digital communication and interaction. Remote digital cultures provide rich and complex tapestries of social conventions, identity development, and human Behavior. These cultures were born and raised in the massiveness of the internet. Innovative methodological techniques that may successfully negotiate the complexities of online environments while encapsulating the spirit of digital communities are necessary to comprehend these cultures. In this effort, ethnographic methodologies prove to be extremely useful instruments, providing comprehensive and thorough understandings of people’s lived experiences in distant digital societies. Data collected from undergraduate students (around 60) to analyze their social interaction with others in university through different technologies to promote social bonds and social relationships. The normative structure of social bonds and relationships has been studied. In research methodology, extensive ethnographic technique required physical immersion in communities to observe rituals, customs, and social interactions firsthand in social relationships. However, researchers have modified their approaches to studying distant digital cultures as digital technologies have altered human interactions increasingly.